Religion and Refugee Well-Being: The Importance of Inclusive Community - Wu, Stephen (Journal for the scientific study of religion, 2021)
We use a large sample of refugees in Utica, New York to investigate how religiosity and the ability to practice religion are related to happiness in one's community. We analyze religious and secular facets of the community in which they live, such as perceived ability to practice their religion, sense of safety, and experiences of discrimination. Contrary to the literature on broader populations, we find that religiosity is unrelated to refugees’ happiness in their community, but their perceived ability to practice is strongly related to this measure of well-being. Ability to practice religion remains strongly related to happiness in the community even for refugees who are not religious and for ones who do not regularly attend services. These findings point to the need for more studies to include measures not only of individual religiosity, but facets of religion in people's larger communities, especially for vulnerable populations like refugees.